2012
DOI: 10.1007/s00401-012-1052-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of PGC-1α partly underlies mitochondrial changes and correlates with neuronal loss in multiple sclerosis cortex

Abstract: There is growing evidence that mitochondrial dysfunction and associated reactive oxygen species (ROS) formation contribute to neurodegenerative processes in multiple sclerosis (MS). Here, we investigated whether alterations in transcriptional regulators of key mitochondrial proteins underlie mitochondrial dysfunction in MS cortex and contribute to neuronal loss. Hereto, we analyzed the expression of mitochondrial transcriptional (co-)factors and proteins involved in mitochondrial redox balance regulation in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
84
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 49 publications
9
84
1
Order By: Relevance
“…The mechanisms involved in cortical pathology are not clear, but current hypotheses describe dysfunction of the mitochondria in the cortex in MS. In studies analyzing postmortem brain tissue, the expression of genes involved in mitochondrial respiration has been found to be altered in normal appearing gray matter (NAGM) in MS brains compared to NAGM in non-diseased brains (Dutta et al 2006; Pandit et al 2009; Witte et al 2013). In a subsequent proteomic analysis of mitochondria in MS and control cortical tissue, hemoglobin β (Hbb) was found to be expressed in neurons and was more abundant in MS postmortem cortex compared to non-diseased cortex (Broadwater et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in cortical pathology are not clear, but current hypotheses describe dysfunction of the mitochondria in the cortex in MS. In studies analyzing postmortem brain tissue, the expression of genes involved in mitochondrial respiration has been found to be altered in normal appearing gray matter (NAGM) in MS brains compared to NAGM in non-diseased brains (Dutta et al 2006; Pandit et al 2009; Witte et al 2013). In a subsequent proteomic analysis of mitochondria in MS and control cortical tissue, hemoglobin β (Hbb) was found to be expressed in neurons and was more abundant in MS postmortem cortex compared to non-diseased cortex (Broadwater et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms responsible for cortical pathology are not clear, but we and others have reported mitochondrial damage in MS cortex. Mitochondrial defects including decreased expression of mitochondrial electron transport chain subunit genes in neurons and cytochrome oxidase inhibition have been reported in normal appearing gray matter (NAGM) in MS (Dutta et al 2006; Pandit et al 2009; Broadwater et al 2011; Campbell et al 2011; Witte et al 2013). It has also been demonstrated that the neuronal metabolite NAA is decreased in the MS brain (Gonen et al 2000; Inglese et al 2004) and that NAA synthesis is regulated by electron transport chain activity (Li et al 2013), suggesting a dysfunction of neuronal metabolism in MS (Cader et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical gray matter pathology, including demyelination, axonal degeneration, and brain atrophy, is recognized as a major factor contributing to disability in MS (Inglese et al, 2004;Bö et al, 2006;Fisher et al, 2008). Previous studies suggest that mitochondrial defects, including reductions in neuronal expression of nuclear encoded mitochondrial electron transport chain genes, decreased synthesis of the neuronal mitochondrial metabolite N-acetylaspartate (NAA), and inhibition of mitochondrial respiration contribute to cortical pathology in MS (Dutta et al, 2006;Pandit et al, 2009;Broadwater et al, 2011;Campbell et al, 2011;Li et al, 2013;Witte et al, 2013); however, the mechanisms involved in these mitochondrial changes are not clear.…”
Section: Introductionmentioning
confidence: 99%